ANALISIS BAHAN AJAR FISIKA SMA KELAS XI DI KECAMATAN INDRALAYA UTARA BERDASARKAN KATEGORI LITERASI SAINS - Feni Kurnia; Zulherman .; Apit Fathurohman (JURNAL INOVASI DAN PEMBELAJARAN FISIKA, 2014)
The aim of this research is to analyze whether high school physics teaching materials which used in grade XI in the District of North Indralaya already represent the Scientific Literacy themes , as well as obtain information on the scope of science of teaching materials in the form of books used in schools in the district of North Indralaya. This research was done using physics teaching materials in the form of books used in grade XI in the District of North Indralaya, namely in SMAN 1 North Indralaya and SMA PGRI. The research found out that the books used in high schools in the District of North Indralaya already represent scientific literacy themes with an average emergence percentage of 59.62 % for the themes of scientific literacy as a knowledge of science, 33.57 % for the themes of literacy sciences as a way of investigating , 5.73 % for the themes of scientific literacy sciences as a way of thinking, and 1.08 % for the themes of the interaction of science, technology with society. From the research, it is advi 43 Jurnal Inovasi dan Pembelajaran Fisika Vol.1 No.1, Mei 2014        ISSN : 2355-7109   sable to conduct further research on the level of scientific literacy of high schools’ students in the district of North Inderalaya that learning with books that have been analyzed .